A Multicenter Collaboration to Assess the Safety of Laparoscopic Ventral Rectopexy. Issue 8 (August 2015) - Evans, Charles; Stevenson, Andrew R. L.; Sileri, Pierpaolo; Mercer-Jones, Mark A.; Dixon, Anthony R.; Cunningham, Chris; Jones, Oliver M.; Lindsey, Ian
Abstract : BACKGROUND: Concerns have been raised regarding the potential risk of mesh complications after laparoscopic ventral rectopexy. OBJECTIVE: This study aimed to determine the risk of mesh and nonmesh morbidity after laparoscopic ventral rectopexy and to compare the safety of synthetic meshes with biological grafts. DESIGN: This was a retrospective review. SETTINGS: The study used data collated from prospective pelvic floor databases in 5 centers (3 in the United Kingdom, 1 in Australia, and 1 in Italy). PATIENTS: All of the patients undergoing laparoscopic ventral rectopexy over a 14-year period (1999–2013) at these centers were included in the study. MAIN OUTCOME MEASURES: The primary outcome was mesh morbidity, classified as vaginal erosion, rectal erosion, rectovaginal fistula, or perineal erosion. Secondary outcomes were nonmesh morbidity. RESULTS: A total of 2203 patients underwent surgery; 1764 (80.1%) used synthetic mesh and 439 (19.9%) used biological grafts. There were 2 postoperative deaths (0.1%). Forty-five patients (2.0%) had mesh erosion, including 20 vaginal, 17 rectal, 7 rectovaginal fistula, and 1 perineal. Twenty-three patients (51.1%) required treatment for minor erosion morbidity (local excision of stitch/exposed mesh), and 18 patients (40.0%) were treated for major erosion morbidity (12 laparoscopic mesh removal, 3 mesh removal plus colostomy, and 3 anterior resection). Erosion occurred in 2.4% of synthetic meshes and 0.7% of biological meshes. The median time to erosion was 23 months. Nonmesh complications occurred in 11.1% of patients. LIMITATIONS: This was a retrospective study including patients with minimal follow-up. The study was unable to determine whether patients will develop future erosions, currently have asymptomatic erosions, or have been treated in other institutions for erosions. CONCLUSIONS: Laparoscopic ventral rectopexy is a safe operation. Mesh erosion rates are 2% and occasionally require resectional surgery that might be reduced by the use of biological graft. An international ventral mesh registry is recommended to monitor mesh problems and to assess whether type of mesh has any impact on functional outcomes or the need for revisional surgery for nonerosion problems.